Healthcare Provider Advocacy for Primary Health Care Strengthening: A Call for Action. (March 2022) - Kuehne, Flora; Kalkman, Laura; Joshi, Shiv; Tun, Wunna; Azeem, Nishwa; Buowari, Dabota Yvonne; Amugo, Chioma; Kallestrup, Per; Kraef, Christian
Primary Health Care (PHC) is the backbone of health systems and a cornerstone of Universal Health Coverage. In 2018, political commitment to PHC, including a comprehensive approach based on essential care throughout the lifespan, integrated public health functions, and community empowerment was reaffirmed by international stakeholders in Astana. As recent events exposed weaknesses of health care systems worldwide, growing attention has been paid to strengthening PHC. While the role of care providers as health advocates has been recognized, they may lack skills, opportunities, and resources to actively engage in advocacy. Particularly for PHC providers, guidance and tools on how to advocate to strengthen PHC are scarce. In this article, we review priority policy areas for PHC strengthening with relevance for several settings and health care systems and propose approaches to empower PHC providers—physician, non-physician, or informal PHC providers—to advocate for strengthening PHC in their countries by individual or collective action. We provide initial ideas for a stepwise advocacy strategy and recommendations for practical advocacy activities. Our aim is to initiate further discussion on how to strengthen health care provider driven advocacy for PHC and to encourage advocates in the field to reflect on their opportunities for local, national, and global action.